Counting blessings and sharing gratitude in a Chinese prisoner sample: Effects of gratitude-based interventions on subjective well-being and aggression. Issue 3 (4th May 2019) - Deng, Yanhe; Xiang, Ruiyang; Zhu, Yijie; Li, Yi; Yu, Shi; Liu, Xiangping
Abstract: Gratitude-based interventions are effective for increasing individuals' subjective well-being (SWB); however, they have not been validated among prisoners, especially for negative states (i.e. aggression). Furthermore, as a social emotion, gratitude might be nurtured via practice within a social group. Therefore, we developed a weekly group-based sharing gratitude exercise, and examined its effect along with that of daily blessing-counting among prisoners in China. Ninety-six male violent prisoners were assigned randomly to three conditions (gratitude-sharing, blessing-counting, and control). Interventions took place over five weeks. Both interventions improved SWB and decreased aggression compared to controls. Additionally, the improvement in gratitude mediated the relationship between the two forms of intervention and SWB. These findings indicate that gratitude-based interventions can be implemented among male prisoners to help further the psychological corrective function of prisons in China.